(3GdYUa GdPgfj (B:s (3eagheg(B-(3CSGdjHg(B-(3eHGOFg (B/s - (3YGeQ, WGQb YHO GdQDha eMeOs; (3GdeUQj, EjgGH YjSis ((3GdbGgQI (B:s (3eDSSI WjHI ddfTQ hGdJhRjY,s, 2017)
(3jJMOK gPG GdcJGH Yf GdYUa GdPgfj eagheg hCSGdjHg heHGOFg hjJfGhd gPG GdcJGH eaghe GdJYdje GdfTW hadSaI GdJYdje GdfTW hfTCI hJWhQ GdJYdje GdfTW hCgOGa GdJYdje GdfTW hahGFO GdJYdje GdfTW hCgejI GdJYdje GdfTW hCSS heHGOF GdJYdje GdfTW hGdMGLI Edi GdJYdje GdfTW hjJMOK GdcJGH CjVG Yf GdaQb Hjf GdJYdje GdfTW hGdJYdje GdJbdjOj hGSJQGJjLjGJ GdJYdje GdfTW heHQQGJ GSJNOGe GdJYdje GdfTW(B.s
(3HHdjhLQGajI (B: (3UaMI (B225-240.s
Keywords: (3GdYUa GdPgfjs; (3GdJacjQs; (3Md GdeTcdGJs